Recuperación de la estructura urbano ambiental como estrategia para el desarrollo del espacio público en el río del oro en la ciudad de Neiva Huila - Galeano Tovar, Laura Valentina (Universidad Antonio Nariño, 2024)
After an analysis of El Río del Oro, it is one of the rivers that crosses the municipal seat of Neiva in an east-west direction, it is born in the Cuchilla Terpella, a branch of the Neiva hill, at 1000 meters above sea level. It was necessary to cover problems found in the area, the abandonment, the misuse that the development of the city and the different uses not allowed have generated serious problems in this area, starting with an economic, social and environmental study of this sector. Based on this analysis, it seeks to propose a proposal on the territory that includes the Rio del Oro, achieving a great impact in a positive way in the city of Neiva (Huila), which arises from the need to rescue the relationship between the city , public space and the gold river, a link that is lost and that could be effective for the sociocultural and economic development of the capital of Huila.